2018
DOI: 10.3390/soc8010008
|View full text |Cite
|
Sign up to set email alerts
|

Young People Engaging in Volunteering: Questioning a Generational Trend in an Individualized Society

Abstract: Today young people experience a world that is being significantly changed by large-scale transformations in education and labour markets. Youth, as a generation, is most affected by those changes, since they are more likely to reshape their ways of living in response to the conditions they face, which inevitably produce inequalities in their lives. Volunteering is one of their responses. This paper aims to discuss the generational motivations and attitudes of a group of 11 European young people to participate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 47 publications
0
19
0
Order By: Relevance
“…The portrait of the current relationship between youth, politics and participation sketched at the beginning of this article described young people who in most cases are not very interested in politics, have difficulty in positioning themselves on the left-right scale, as well as in finding a political party among the existent ones as a personal point of reference They also express very low trust in the political system and in its institutions and actors, in particular political parties and politicians. As a logical consequence, they tend to be weakly involved in institutional forms of participation (the only exception being voting), and even if most of them express interest in issues of collective relevance, and are able to define socially relevant goals for politics, only a very narrow minority define themselves as politically engaged, although a wider sector is involved in various forms of social engagement, and a smaller but considerable sector is also involved in several forms of occasional non-institutional activities of political participation [1][2][3][4][5][6]9,[24][25][26][27][28][29][30][31][32][33][34][35][36][37][38].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The portrait of the current relationship between youth, politics and participation sketched at the beginning of this article described young people who in most cases are not very interested in politics, have difficulty in positioning themselves on the left-right scale, as well as in finding a political party among the existent ones as a personal point of reference They also express very low trust in the political system and in its institutions and actors, in particular political parties and politicians. As a logical consequence, they tend to be weakly involved in institutional forms of participation (the only exception being voting), and even if most of them express interest in issues of collective relevance, and are able to define socially relevant goals for politics, only a very narrow minority define themselves as politically engaged, although a wider sector is involved in various forms of social engagement, and a smaller but considerable sector is also involved in several forms of occasional non-institutional activities of political participation [1][2][3][4][5][6]9,[24][25][26][27][28][29][30][31][32][33][34][35][36][37][38].…”
Section: Discussionmentioning
confidence: 99%
“…Youth activism in political squats is characterized by the same mix of self-satisfaction and attention to "the other", of auto-and hetero-orientation, as well as by the same high levels of flexibility and organizational elasticity, as several other current forms of juvenile participation [3,5,6,24,26,31]. 9 Our research clearly shows this mix, considering not only individual motivations but also collective activities and organizational processes: The proposal of a venture, its characteristics, the division of tasks and roles, have come out as the result of the interplay between collective aims and forms of action with individual sensitivities and preferences, without any hierarchical imposition or any stabilized, formal definition.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…War. Many scholars have suggested that civic and political apathy are most prevalent among young people (Banaji & Buckingham, 2010;Dalton, 2008;Dudley & Gitelson, 2003;Lewis, 2001), but others have argued that the nature of civic participation was changing, with young people turning to less formal and less conventional forms of participation (Furlong & Cartmel, 2007;Harris, Wyn, & Younes, 2010;Jardim & da Silva, 2018), engaging in a more social and less political manner (Zuckerman, 2014) and using social networks (Banaji & Buckingham, 2010;Bennett, 2003;Coleman, 2008;Zukin, Keeter, Andolina, Jenkins, & Delli Carpini, 2006). Furthermore, democracies are also facing problems of social exclusion and lack of social cohesion (Nelson & Kerr, 2006;Schmeets & Coumans, 2013;Schultz, Ainley, Fraillon, Kerr, & Losito, 2010).…”
mentioning
confidence: 99%